Influence of varieties and nutrient management practices on productivity, nutrient acquisition and resource-use efficiency of rice (Oryza sativa) in North-eastern hill region of India - N, HARISH M; CHOUDHARY, ANIL K; SINGH, Y V; POONIYA, VIJAY; DAS, ANUP; T, VARATHARAJAN; BABU, SUBHASH (The Indian Journal of Agricultural Sciences, 2019)
It is concluded that the INM practice and rice variety Shahsarang 1 showed their superiority over their respective counterparts, i.e. other nutrient management practices and rice varieties w.r.t. crop productivity, NPK acquisition behavior in rice grains and straw visâ€“Ã â€“vis NPK uptake, and resourceâ€“use efficiency in current study. Thus, INM practice and rice variety Shahsarang 1 can be recommended to the resource-poor hill farmers for enhancing rice productivity, plant nutrient acquisition and resourceâ€“use efficiency in north-eastern hill region of eastern Himalayas.